2009
DOI: 10.5014/ajot.63.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Occupation of Motherhood: Challenges for Mothers With Scleroderma

Abstract: Mothers with scleroderma have difficulty with aspects of motherhood. The findings that pain, fatigue, and activity limitations were related to mothering suggest areas for occupational therapy intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 22 publications
3
35
1
2
Order By: Relevance
“…The findings supported those of previous studies [11][12][13] indicating that mothers with disabilities face physical challenges such as caring tasks, household chores, and outdoor activities with the children. The findings also revealed mental challenges that influenced and were influenced by the physical challenges.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The findings supported those of previous studies [11][12][13] indicating that mothers with disabilities face physical challenges such as caring tasks, household chores, and outdoor activities with the children. The findings also revealed mental challenges that influenced and were influenced by the physical challenges.…”
Section: Discussionsupporting
confidence: 95%
“…Poole et al [13] quantitatively examined the parenting ability, pain, fatigue, and activity limitations of 75 mothers with scleroderma (SSc) who had a child between birth and 18 years old. Mothers with SSc reported difficulty with parenting.…”
Section: Introductionmentioning
confidence: 99%
“…The most difficult tasks for these mothers included playing games with a child, shopping with a child, and doing household chores. Because some studies reported that mothers with younger children have greater difficulty compared to mothers with older children [11][12][13]19], we had thought that mothers with SLE who had younger children (birth −5 years) would have more difficulties with parenting than mothers who had older children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Contrary to our expectations, mothers with younger children reported less difficulty with parenting.…”
Section: Discussioncontrasting
confidence: 83%
“…These tasks include picking up and carrying a child, getting up and down from the floor to play, doing household tasks, and shopping. However, having energy to talk/listen to a child was the most difficult task reported by mothers with SLE who had young children, whereas mothers with RA and SSc reported getting up and down from the floor, picking up and carrying a child, and feeding tasks as the most difficult [12,19]. One explanation of this discrepancy may be the severe level of fatigue reported by mothers with SLE.…”
Section: Discussionmentioning
confidence: 52%
“…В связи с этим в настоящее время уде-ляется большое внимание разработке, апробации и вне-дрению доступных методов реабилитации больных ССД, которые будут способствовать улучшению КЖ данной категории пациентов [35,36]. Необходимость таких иссле-дований подтверждается рядом работ, в которых было показано, что больные ССД испытывают трудности при работе с компьютером, уходе за детьми и ведении домаш-них дел [37,38]. На основании полученных результатов авторы этих публикаций пришли к выводу, что пациенты с ССД нуждаются в адаптации к повседневной деятельности и отдыху, но для разработки оптимальных стратегий, учи-тывающих специфику этого заболевания, необходимы высококачественные исследования.…”
Section: о б з о р ыunclassified